Comparison of the efficacy and cost‐effectiveness of an immunologically targeted low‐dose rituximab protocol with the conventional rheumatoid arthritis protocol in severe pemphigus. (25th June 2022) - Singh, Namrata; Handa, Sanjeev; Mahajan, Rahul; Sachdeva, Naresh; De, Dipankar
Abstract: Background: Various dosing protocols of rituximab have been used in pemphigus. B‐cell repopulation following rituximab treatment can be considered a forerunner of clinical relapse. Immunologically guided dosing may remove the need for fixed timepoint maintenance dosing, hence being more cost‐effective and perhaps safer. Aim: To compare the overall efficacy and cost‐effectiveness of a low‐dose rituximab regimen (500 mg, 2 weeks apart) with immunologically guided, ultralow‐dose (200 mg) top‐up infusions on immunological relapse vs. the use of a rheumatoid arthritis (RA) protocol with rituximab 500 mg repeat infusion to treat clinical relapse in severe pemphigus, over a 1‐year period, Methods: In total, 23 patients with severe pemphigus were randomized into Group A (RA protocol: 1000 mg given as two doses, 2 weeks apart) and Group B (low‐dose rituximab 500 mg given as two doses, 2 weeks apart). Both groups also received short‐term oral corticosteroids, and underwent clinical and immunological (3‐monthly flow cytometry assessments of B‐cell subtypes) monitoring. Group A received a top‐up dose of rituximab 500 mg upon clinical relapse, while Group B received an ultralow top‐up dose (200 mg) following detection of B‐cell repopulation, which was intended to prevent clinical relapse. Outcome parameters [complete remission off treatment (CROT), relapse (clinical and immunological), total corticosteroid dose and direct cost of therapy] were compared. Results: The mean ± SD time to CROT (Group A, 27.1 ± 1.6 weeks; Group B, 26 ± 1.2 weeks, P = 0.09) and the cumulative prednisolone dose ( P = 0.28) were comparable between the two groups. In Group A, 3 of 9 (33.3%) patients had clinical relapse (mean ± SD time of 9.3 ± 0.4 months). In Group B, B‐cell repopulation was seen in 10 of 11 (90.9%) patients within a mean time of 8.4 ± 2.4 months, and a single top‐up dose of 200 mg successfully prevented clinical relapse. The overall cost of therapy was 37.4% cheaper in Group B. Conclusion: An immunologically guided low‐dose rituximab regimen can be an equally effective but more affordable alternative to conventional rituximab regimens in pemphigus. Abstract : As yet, there is no universally accepted rituximab dosing protocol for pemphigus. An immunologically guided low‐dose rituximab protocol can provide an equally effective, yet more cost‐effective and safer regimen compared with conventional rituximab regimens in severe pemphigus, and can help in tailoring patient treatment based on their B‐cell repopulation characteristics following rituximab infusion.